Pengaruh Faktor - Faktor Good Corporate Governance Terhadap Pengungkapan Corporate Social Responsibility Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2011 - 2013 - Puspa Ningrum, Lisanti; , Dr. Erma Setiawati, M.M., Akt., CA (2015)
The purpose of this study to examine the effect of managerial ownership on the disclosure of corporate social responsibility. To test the effect of institutional ownership on the disclosure of corporate social responsibility. To test the effect of foreign ownership on the disclosure of corporate social responsibility. To test the effect of independent board size on the disclosure of corporate social responsibility. To test the effect of audit committee size on the disclosure of corporate social responsibility. To test the effect of concentrated share ownership on the disclosure of corporate social responsibility. The samples are manufacturing companies listed in Indonesia Stock Exchange disclosure of corporate social responsibility and had complete data on managerial ownership, institutional ownership, foreign ownership, independent board size, audit committee size, and concentrated share ownership consistently during the period 2011 - 2013. The number of samples used by 12 companies manufacturing for 3 consecutive years - helped. This study used a descriptive statistical analysis, classical assumption test in the form of normality test, multicollinearity test, autocorrelation test, heteroscedasticity test and hypotheses test in the form of multiple linear regression analysis test, t statistic test, F statistic test, coefficient of determination (R²) test. The results of this study showed that the variables that effect on the disclosure of corporate social responsibility in manufacturing companies are managerial ownership, institutional ownership, and independent board size as evidenced by the significant value < 0,05 while the variables does not effect on the disclosure of corporate social responsibility in manufacturing companies are foreign ownership, audit committee size, and concentrated share ownership as evidenced by the significant value > 0,05